Effects of 6 months glucagon‐like peptide‐1 receptor agonist treatment on endothelial function in type 2 diabetes mellitus patients. Issue 8 (27th March 2013) - Hopkins, N. D.; Cuthbertson, D. J.; Kemp, G. J.; Pugh, C.; Green, D. J.; Cable, N. T.; Jones, H.
<x xml:space="preserve">Abstract</x> Glucagon‐like peptide‐1 receptor agonists (GLP‐1 RA) are used for treatment in type 2 diabetes mellitus (T2DM). Little is known about their cardiovascular (CV) impact. We sought to determine the effects of chronic treatment on vascular function in T2DM. Brachial artery endothelial‐dependent flow‐mediated dilation (FMD) and endothelial‐independent glyceryl trinitrate (GTN) function and carotid intima‐medial thickness (cIMT) were assessed in 11 severely obese T2DMs (4 females, 7 males: 55 ± 8 years, diabetes duration 8.3 ± 4.7 years mean ± s.d.) before and after 6 months GLP‐1 RA. Body weight (5.3 ± 1.2 kg; p < 0.05) and magnetic resonance imaging determined total and subcutaneous fat, but not visceral fat, decreased. Glycaemic control improved. There were no significant changes in FMD, GTN and cIMT (−1.1 ± 0.4%, 0.3 ± 3.0% and 0.00 ± 0.04 mm, respectively). Despite significant improvements in body composition and glycaemic control, 6 months GLP‐1 RA treatment did not modulate vascular function. Alternative strategies may therefore be needed to reduce the burden of CV risk in severely obese patients with long‐standing T2DM.